Penerapan Sanksi Hukum Adat Ukun Badu Terhadap Pelaku Pencurian Kayu di Hutan Lindung Desa Sikun Kecamatan Malaka Barat Kabupaten Malaka - Manuk, Weldo Susanto; Medan, Karolus Kopong; Pello, Jimmy (Law Faculty, Nusa Cendana University, 2024)
The implementation of customary sanctions in Sikun Village, Malacca Regency makes customary sanctions a matter that invites pros and cons in the relationship of indigenous peoples because each perpetrator feels that the customary sanctions imposed on him are very detrimental. Researchers aim to determine the application of Ukun Badu customary law sanctions against perpetrators of theft in Sikun Village, as well as to find out the obstacles in applying Ukun Badu sanctions against perpetrators of theft in Sikun Village. The research method used is empirical juridical. This research approach is a case and conceptual approach. The results showed the application of Ukun Badu customary sanctions against perpetrators of timber theft in Sikun Village, through the process of determining the time of trial, identifying evidence based on witness reports, questions and answers with perpetrators, through customary deliberation, imposing decisions following fines under applicable customary law, handing over sanctions. What hinders the application of Ukun Badu customary sanctions on perpetrators of timber theft cases in the Sikun Village Protection Forest is that the perpetrators do not approve of the perpetrators not being present at the trial, the victims do not approve and lack of a sense of justice for the community, and obstacles on the part of traditional leaders in giving sanctions to perpetrators are not carried out properly. The author suggests that the community when experiencing a problem should be resolved first according to applicable customary law.